Comparative incidence and outcomes of COVID‐19 in kidney or kidney‐pancreas transplant recipients versus kidney or kidney‐pancreas waitlisted patients: A single‐center study - Santos, Carlos A. Q. (Clin Transplant, 2021)
BACKGROUND: COVID‐19 epidemiologic studies comparing immunosuppressed and immunocompetent patients may provide insight into the impact of immunosuppressants on outcomes. METHODS: In this retrospective cohort study, we assembled kidney or kidney‐pancreas transplant recipients who underwent transplant from January 1, 2010, to June 30, 2020, and kidney or kidney‐pancreas waitlisted patients who were ever on the waitlist from January 1, 2019, to June 30, 2020. We identified laboratory‐confirmed COVID‐19 until January 31, 2021, and tracked its outcomes by leveraging informatics infrastructure developed for an outcomes research network. RESULTS: COVID‐19 was identified in 62 of 887 kidney or kidney‐pancreas transplant recipients and 20 of 434 kidney or kidney‐pancreas waitlisted patients (7.0% vs. 4.6%, p = .092). Of these patients with COVID‐19, hospitalization occurred in 48 of 62 transplant recipients and 8 of 20 waitlisted patients (77% vs. 40%, p = .002); intensive care unit admission occurred in 18 of 62 transplant recipients and 2 of 20 waitlisted patients (29% vs. 10%, p = .085); and 7 transplant recipients were mechanically ventilated and died, whereas no waitlisted patients were mechanically ventilated or died (11% vs. 0%, p = .116). CONCLUSIONS: Our study provides single‐center data and an informatics approach that can be used to inform the design of multicenter studies.